DAKWAH DINAMIS DALAM MEMBANGUN KOMUNITAS MASYARAKAT DESA YANG HARMONIS STUDI TOKOH KH.FATHUR ROZI - Muzdalifah; Nazahah Ulin Nuha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Dakwah plays a significant role in maintaining and strengthening social harmony in rural communities, particularly in Patokan Village, Bantaran District, Probolinggo Regency. In the context of village society, dakwah functions not only as a medium for conveying Islamic teachings but also as a means of social development and reinforcement of communal values. This study aims to analyze the role of dynamic dakwah in fostering social harmony within the community. The research employs a qualitative approach using a biographical study method. Data were collected through in-depth interviews with Kyai Haji Fathur Rozi, village residents, students (santri), and other parties involved in dakwah activities, complemented by direct observation of the ongoing dakwah practices. The findings reveal that the dynamic dakwah implemented by Kyai Haji Fathur Rozi contributes significantly to the creation of a harmonious, peaceful, and tolerant social life. This contribution is reflected in a persuasive, inclusive, and culturally adaptive preaching approach, the strengthening of universal Islamic values, the development of community moral character, and active involvement in mitigating social conflicts. Therefore, contextual and community-based dynamic dakwah is proven to be effective in reinforcing social harmony in rural communities